Potensi Penerapan Transit Oriented Development Dalam Meningkatkan Pengguna Transportasi Publik: (Studi Kasus : Stasiun Depok Baru) - Suryobuwono, Abdullah Ade; Marpaung, Edward; Permana, Luh Putri Septia (Jurnal Sistem Transportasi & Logistik, 2024)
Transportation problems greatly affect the growth of community mobility, land use as a support for transportation. The purpose of this study is to determine the potential for implementing Transit Oriented Development (TOD) so that it is easily accessible to commuter line service users and makes it easier to transfer modes, the analysis method uses PTV Vissim software, SPSS (Statistical Package for the Social Sciences), Geoffrey's statistical test E. Havers (GEH). Jalan Margonda Raya 2023 (Existing) is known to have a Level Of Service C with an average free flow speed of 45.39 Km/hour with a capacity of 4086.72 cur/hour, the degree of saturation (DS) value is 0.7 . the results of the calculation of stopped vehicles, obtained an average value of 0.99 seconds for stopped vehicles, a minimum value of 0.99 seconds, and a maximum value of 0.99 seconds. From the results of calculating vehicle speed, an average value of 21.51 km/hour is obtained, a minimum value of 21.51 km/hour and a maximum value of 21.51 km/hour. All GEH calculated values generated from data are smaller than 5 (<5 GEH) means that there is no significant difference for the data pair and the model is declared valid. The application of TOD at the new Depok station is reviewed from 8 aspects of TOD. It is considered to have the potential to apply Transit Oriented Development.